FAKTOR-FAKTOR PENYEBAB ANAK SUKU AKIT TIDAK BERSEKOLAH - Khairafi Qaribi; Zufan Saam; Tri Umari (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: Education is very important for human life with human education getting knowledge as capital in carrying out life, especially to survive through the times that are progressing more and more, based on the background of many tribal people many children who do not attend school and the picture of tribal family life akit therefore the researcher feels the need to examine the family of akit tribes who are not attending school and the description of the akit tribe profile, the research method using qualitative methods and random sampling, data use techniques using observation and interview techniques with a population of 133 family heads with a sample of 30 families . The results of the study showed that the number of children who did not attend school were caused by economic factors and the distance of their homes to school was very far while many of their parents did not go to school and many did not finish school. For the daily income of the akit family, they were charcoal workers. Keywords: Akit tribe children who do not attend school